Activin-A impairs CD8 T cell-mediated immunity and immune checkpoint therapy response in melanoma. Issue 5 (17th May 2022) - Pinjusic, Katarina; Dubey, Olivier Andreas; Egorova, Olga; Nassiri, Sina; Meylan, Etienne; Faget, Julien; Constam, Daniel Beat
Abstract : Background: Activin-A, a transforming growth factor β family member, is secreted by many cancer types and is often associated with poor disease prognosis. Previous studies have shown that Activin-A expression can promote cancer progression and reduce the intratumoral frequency of cytotoxic T cells. However, the underlying mechanisms and the significance of Activin-A expression for cancer therapies are unclear. Methods: We analyzed the expression of the Activin-A encoding gene INHBA in melanoma patients and the influence of its gain- or loss-of-function on the immune infiltration and growth of BRAF -driven YUMM3.3 and iBIP2 mouse melanoma grafts and in B16 models. Using antibody depletion strategies, we investigated the dependence of Activin-A tumor-promoting effect on different immune cells. Immune-regulatory effects of Activin-A were further characterized in vitro and by an adoptive transfer of T cells. Finally, we assessed INHBA expression in melanoma patients who received immune checkpoint therapy and tested whether it impairs the response in preclinical models. Results: We show that Activin-A secretion by melanoma cells inhibits adaptive antitumor immunity irrespective of BRAF status by inhibiting CD8 + T cell infiltration indirectly and even independently of CD4 T cells, at least in part by attenuating the production of CXCL9/10 by myeloid cells. In addition, we show that Activin-A/ INHBA expression correlates with anti-PD1 therapy resistance in melanoma patients and impairs the response to dual anti-cytotoxic T-Lymphocyte associated protein 4/anti-PD1 treatment in preclinical models. Conclusions: Our findings suggest that strategies interfering with Activin-A induced immune-regulation offer new therapeutic opportunities to overcome CD8 T cell exclusion and immunotherapy resistance.